Adaptation mechanisms of Brucella abortus to low magnesium ion stress - Hengtai Wang; Lang Lv; Yike Huang; Hui Jiang; Xiaowen Yang; Jiabo Ding; Liangquan Zhu; Lei Xu; Huaiming Sang; Jianxia Jiang; Nan Wang; Peng Li (BMC Veterinary Research)
Abstract Background Brucella abortus, a facultative intracellular pathogenic bacterium that usually causes diseases under animals and humans, can survive and replicate within phagocytic cells. Within the host cells, B. abortus has to adapt to low cytosolic magnesium ion (Mg2+) environment, which is critical for bacterial survival and replication. To understand the fitness of B. abortus under the low Mg2+ environment, transcriptome analysis was performed by RNA-seq. Results: 262 differentially expressed genes (DEGs, fold-change > 1.5 and p < 0.05) of B. abortus, 123 significantly upregulated genes and 139 significantly downregulated genes, were identified under Mg2+ starvation environment, highlighting that B. abortus probably employed large amounts of factors to support the adaptation of low Mg2+ stress responses. Amongst them, two key genes, BAB_RS26550 (encoding putative protein, abbreviated as HP3) and BAB_RS26555 (encoding MgtC/SapB family protein, abbreviated as MgtC), was associated with the ATP hydrolysis to maintain the growth and metabolism of B. abortus under Mg2+ starvation environment. Furthermore, the HP3 supported B. abortus to resist bactericidal polycations and polymyxin B, as well as influenced the biofilm formation of B. abortus. However, HP3 does not appear to have an appreciable effect on the B. abortus virulence. Conclusions: In this study, a first description of the pattern of B. abortus genetic expression in response to low Mg2+ stress response provides insights into the intracellular behavior of B. abortus at the genetic level.